The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1128/jvi.79.22.13900-13914.2005
|View full text |Cite
|
Sign up to set email alerts
|

Expression and Mutational Analysis of Autographa californica Nucleopolyhedrovirus HCF-1: Functional Requirements for Cysteine Residues

Abstract: The host cell-specific factor 1 gene (hcf-1) of the baculovirus Autographa californica multiple nucleopolyhedrovirus is required for efficient virus growth in TN368 cells but is dispensable for virus replication in SF21 cells. However, the mechanism of action of hcf-1 is unknown. To begin to understand its function in virus replication we have investigated the expression and localization pattern of HCF-1 in infected cells. Analysis of virus-infected TN368 cells showed that hcf-1 is expressed at an early time i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…The hcf-1 gene of AcMNPV is one of the lef (late expression factor) genes, which is essential for viral DNA replication and expression of late genes in transient assays in Tn368, but not Sf21, cells 14 . In AcMNPV-infected Tn368 cells, the HCF-1 protein is synthesized early during infection and localizes in punctuate nuclear structures 17 , 18 . Recombinant AcMNPV defective in functional hcf-1 gene replicates normally in Sf21 cells, but exhibits various mutant phenotypes in Tn368 cells, including defective viral DNA replication and late gene transcription, and complete cessation of cellular and viral protein syntheses 15 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The hcf-1 gene of AcMNPV is one of the lef (late expression factor) genes, which is essential for viral DNA replication and expression of late genes in transient assays in Tn368, but not Sf21, cells 14 . In AcMNPV-infected Tn368 cells, the HCF-1 protein is synthesized early during infection and localizes in punctuate nuclear structures 17 , 18 . Recombinant AcMNPV defective in functional hcf-1 gene replicates normally in Sf21 cells, but exhibits various mutant phenotypes in Tn368 cells, including defective viral DNA replication and late gene transcription, and complete cessation of cellular and viral protein syntheses 15 .…”
Section: Discussionmentioning
confidence: 99%
“…In recombinant AcMNPV defective in the hcf-1 gene, however, productive infection only occurs in Sf21 cells, indicating that AcMNPV requires HCF-1 for the productive infection of Tn368 cells 14 , 15 . The HCF-1 protein contains a putative RING-finger domain, which is involved in the formation of functional HCF-1 dimers or higher-order structures in the nucleus of infected Tn368 cells 17 , 18 . It was also demonstrated that transiently expressed HCF-1 protein represses expression from the hcf-1 promoter and this repression activity of HCF-1 is required for the efficient expression of viral late genes and production of polyhedra in Tn368 cells 18 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutational analysis of hcf-1 function in AcMNPV infection implicates the RING-finger domain in its ability to support virus replication and to self-associate (132).…”
Section: Cellular Host-rangementioning
confidence: 99%
“…Whether it might have a more definitive effect on larval hostrange in another host species has not been determined.It would be interesting to determine if the addition of hcf-1 to the BmNPV genome would affect its ability to infect T. ni cells. Although the specific role for hcf-1 in infection is still unclear, its activity appears to require self-association and nuclear localization (51).Hcf-1 nuclear staining is diffuse in transfected cells but shows distinct punctate foci in infected cells, suggesting that it may localize to promyelocytic leukemia (PML) nuclear bodies(132).…”
mentioning
confidence: 99%